HYBRIDITY ACROSS LINGUISTIC STUDIES - Marsandi Manar (UIBU, 2022)
This study investigates the hybridity across linguistic studies from 2017 to 2019. It specifically attempts to figure out the trends of hybrid linguistic areas. To have a clear insight into the issue, a qualitative text analysis was adopted as the design of study. As the data sources, 304 research articles in linguistics were successfully retrieved from the digital data bases of internationally reputable linguistic journals. From each year, the newest released articles were purposively selected as the data sources. To have the clear insight into the hybrid areas across linguistic studies, the initial analysis was carried out on the titles of research articles. Further, the analysis was also conducted on the abstracts and research questions. Based on the analysis on the titles, abstracts and research questions, it was found that there were 16 types of hybridity across linguistic studies from 2017 to 2019. The two most frequent hybrid linguistic fields in sequence encompass ‘critical discourse analysis + multimodality’ and ‘critical discourse analysis + systemic functional linguistics’. It is expected that the results of this study contributes to provide the insight into the possibility of mixing different areas of linguistic studies as a way of solving human’s growing complex humanistic problems.